Kegiatan Trauma Healing Anak Yatim dan Disabilitas bagi Korban Covid-19 di Kabupaten Bombana - Muh. Najib Husain; Rahman Ako; Iriyani Astuti Arief; Dewi Anggraini (CV. Literasi Indonesia, 2022)
This Internal Community Service Program aims to increase self-confidence and be able to return to normal life in the community. For this reason, the service team carries out Trauma Healing activities in the form of consultations and simulations for Covid-19 victims. This was done considering the unstable condition of the Covid-19 victims who took 3 months in a period of trauma due to the disease caused by the Covid-19 Virus and the views of the community and the nuclear family environment who saw the victims of Covid-19 as a disgrace, especially until now. Through consultation and simulation methods, the service team will transfer knowledge and values to the victims of Covid-19 Adults and the Elderly with the help of media such as posters and materials in the form of power points. In this service activity, the team collaborates with partners, namely the Indonesian Multi Talenta Psychologist Foundation and the Bombana District Health Office. The service team will carry out Trauma Healing activities for Covid-19 victims through the Head of the Indonesian Multi Talented Psychologist Foundation and the Bombana District Health Office so that the role of partners starts from providing information to Covid-19 victims regarding this service activity. At the time of the activity later, partners also play a role in opening service activities and guiding discussion activities with participants. Through collaboration between the service team and partners, it is hoped that the objectives of this activity will be achieved.